An Efficient Aqua-Based Culture Method for the Propagation of High-Quality Arundo donax Seedlings - Jialin Guo; Wei Li; Gangqiang Cao; Luyue Zhang; Zhengqing Xie; Weiwei Chen; Gongyao Shi; Fang Wei; Baoming Tian (Agronomy, 2024)
Arundo donax (family: Poaceae) is a perennial rhizomatous plant with considerable economic and ecological benefits. The plant is characterized by its fast growth, high yield, wide adaptability, and strong disease resistance. However, widespread cultivation is difficult because A. donax can only be asexually propagated. This study tested the efficacy of an aqua-based culture method with short duration and high rooting rate. The aqua-based culture protocol involved treating cane fragments with the commercial broad-spectrum rooting powder ABT-1 (No. 1 of the ABT series) at 100 mg/L for 24 h, followed by culturing in tap water for 19 days. We found that plant materials sampled from September to February of the following year were more suitable for aqua-based culturing than materials sampled from other months. Nodes on different parts of the cane did not vary significantly in the ability to form seedlings. The rooting percentage reached >95% after only 20 days, while the sprouting percentage was >93%. The seedlings obtained were strong, with high survival rates during cultivation and acclimation. No strict requirements for the growing media were necessary to achieve these results. In conclusion, this study provides an empirical foundation for a technique that could facilitate the factory production of high-quality A. donax seedlings.